Sea‐Urchin‐MnO2 for Broadband Optical Modulator. Issue 22 (28th August 2022) - Han, Yueheng; Li, Xiaohui; Chen, Enci; An, Mingqi; Song, Zhuoying; Huang, Xiangzhen; Liu, Xinfeng; Wang, Yishan; Zhao, Wei
Abstract: Manganese dioxide (MnO2 ) is considered to be one of the nanomaterials with enormous value in research and application because of its high theoretical specific capacitance, large specific surface area and porosity, excellent electron transfer ability, and excellent light absorption ability. However, exploring superior nonlinear absorption of MnO2 in the broadband spectrum is still the key challenge to harvesting their greatest potential. In this paper, the optical modulator based on MnO2 is fabricated, and its nonlinear optical performance is measured. The results indicate that the modulation depth is 4.4% and the saturable intensity is 32.8 MW cm −2 at 1.5 µm region. What's more fascinating is that the modulator based on MnO2 is integrated into Er‐doped and Tm‐doped fiber resonators to successfully demonstrate its broadband mode‐locking operations. The coexistence of harmonic bound state pulse and conventional soliton pulse, as well as dual‐wavelength solitons, have been obtained in a communication window and conventional soliton in a 2 µm‐band can be also achieved. This demonstrates that MnO2 serves as a broadband optical modulator, which makes MnO2 more competitive in the future ultrafast photonics and helps to expand the frontier of photonic technology. Abstract : Considering its large specific surface area and porosity, excellent electron transfer ability, and excellent light absorption ability, the broadband optical modulator based on MnO2 is fabricated and applied to fiber lasers. The ultrafast pulse output is realized in the communication window and 2‐µm band, respectively. This demonstrates that MnO2 is more competitive in the future of ultrafast photonics.